Influence of a macrolide antibiotic, roxithromycin, on mast cell growth and activation in vitro - Toshikazu Shimane; Kazuhito Asano; Mayumi Suzuki; Tadashi Hisamitsu; Harumi Suzaki (Mediators of Inflammation)
Background: Long-term administration of macrolide antibiotics is recognized to be able to favorably modify the clinical condition of inflammatory diseases, such as diffuse panbronchiolitis and cystic fibrosis. However, the precise mechanisms by which macrolide antibiotics could improve clinical conditions of the patients are not well understood.